THE INFLUENCE OF COMPENSATION AND ORGANIZATIONAL CULTURE TO THE COMMITMENT OF EMPLOYEES OF PT. DEWANASRI JAYA: THE INFLUENCE OF COMPENSATION AND ORGANIZATIONAL CULTURE TO THE COMMITMENT OF EMPLOYEES OF PT. DEWANASRI JAYA - Wiguna, Deden Hendra; Hasanah, Hasanah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to test and analyze Compensation and Organizational Culture on Employee Commitment at PT. Dewanasri Jaya. The independent variables used are Compensation and Organizational Culture while the dependent variable used is Employee Commitment. The data collection method in this study was carried out by distributing questionnaires to 53 respondents at PT. Dewanasri Jaya. The research method used is a quantitative method that is associative using primary data. These results indicate that compensation and organizational culture have a positive effect on employee commitment. The compensation variable has a positive and significant effect on employee commitment at PT. Dewanasri Jaya, because the t-count value is greater than the t-table with a value of 2.503> 2.008. The organizational culture variable has a positive and significant effect on employee commitment at PT. Dewanasri Jaya, because the t-count value is greater than the t-table with a value of 3.329> 2.008. The compensation and organizational culture variables have a significant effect on employee commitment at PT. Dewanasri Jaya. Based on the results of the F test, the Fcount value > Ftable (39.284 > 3.19) with a significant value of 0.000 smaller than 0.05 or 5%.